Immunobiology of Acquired Resistance to Ticks - Karasuyama, Hajime; Miyake, Kensuke; Yoshikawa, Soichiro (Frontiers in Immunology, 2020)
Ticks are blood-feeding arthropods of great medical and veterinary importance worldwide. They are second to mosquitos as vectors of pathogens that cause serious infectious disorders, including Lyme borreliosis and tick-borne encephalitis. Hard (Ixodid) ticks take a blood meal from hosts over a period of several days and inject saliva together with pathogens to hosts during blood feeding. Some species of animals can develop resistance to tick feeding after a single or repeated tick infestation, manifested by reduced numbers and weights of engorged ticks or tick death. Of note, this acquired tick resistance (ATR) can reduce the chance of pathogen transmission from infected ticks to hosts. This is the basis for the development of tick antigen-targeted vaccines to prevent tick infestation and tick-borne diseases. Basophil accumulation is detected at the tick re-infestation site of animals showing ATR, and basophil depletion abolishes ATR in guinea pigs and mice, illustrating the crucial role for basophils in the expression of ATR. In this review article, we summarize recent advances in our understanding of the cellular and molecular mechanisms underlying ATR with a particular focus on the role of basophils.